Partycypacja a lokalny system polityczny - Pokładecki, Jacek (Eastern Review, 2018)
In Poland the process of decentralization of power started in 1990.As a consequence it resulted in the restoration of local government. The efficiency and effectiveness of the decentralized political system is directly connected with the institution of local government, which is an important element of a democratic state.Local government is a special form of public authority, binding the local community and acting to merge local institutions into one functional unit, which determines the local political system.In addition, an important activity of political self-government is implementetion of the economic mission, attention to quality and living standards by providing public services, social and economic development.